Data governance maturity and employee perception of business intelligence in selected fintech firms in Nigeria: The mediating role of data quality - Adeyemi, Omolade Sunday; Olarewaju, Samuel Oluwakayode; Adeyemi, Oluwatoyin Damilola (UIR Press, 2026)
Purpose: This study examined whether data governance maturity (DGM) predicts employee perception of business intelligence performance (EPBI) in selected fintech firms in Nigeria, the mediating role of data quality (DQ). Design/methodology/approach: A survey of 342 employees from Nigerian fintech firms across data/analytics, IT, compliance, and management was conducted. SEM in AMOS tested hypothesised paths using maximum likelihood and 5,000 bootstrap samples. Findings: DGM positively predicted DQ and DQ positively predicted EPBI. The indirect effect of DGM on EPBI through DQ was statistically significant and consistent with full mediation. DGM explained forty-eight percent of the variance in DQ, whilst DQ accounted for thirty-eight percent of the variance in EPBI. Limitations and Research implications: The cross-sectional research design constrains causal inference, and restricting the sample to Nigerian fintech organisations limits broad generalisability. Future work should deploy longitudinal designs and multi-country samples across other African fintech markets. Practical Implications: Fintech organisations aiming to improve how employees perceive and utilise BI systems must treat data governance as a strategic capability rather than a regulatory formality. Governing data well is the antecedent through which data quality, and eventually employee BI performance perception, is achieved. Originality/value: This study is among the first to empirically model the DGM-DQ-EPBI pathway in the Nigerian fintech sector, extending information quality theory and the resource-based view to a high-growth, data-intensive, African financial services context.